Models as written corrective feedback: Effects on young L2 learners’ fluency in digital writing from product and process perspectives - Criado, Raquel; Garcés-Manzanera, Aitor; Plonsky, Luke (Studies in Second Language Learning and Teaching, 2022)
This study was motivated by Truscott’s (1996, 2004) scarcely empirically tested claims that written corrective feedback (WCF) processing hinders fluency in subsequent rewriting owing to learners’ purposeful avoidance of making mistakes by composing shorter texts at a higher speed. It examined the writing fluency of the texts produced by eighteen 10-11-year-old L2 English children in a digital environment. They were divided into a feedback (N = 10) and a self-correction group (N = 8). Both groups engaged in a three-stage task: writing, comparison of their texts with a model or self-editing as appropriate, and rewriting. Fluency was analyzed via five product/offline and five process/online measures. The texts and writing behaviors were recorded with Inputlog 8.0. The results partially support Truscott’s claims. The feedback group improved their fluency in all the ten measures. However, the self-editing group showed higher fluency than the feedback group in seven of the ten measures, with the corresponding Hedge’s effect sizes between groups ranging from small to large. The study enlightens our knowledge of young learners’ writing fluency and supports adopting a multidimensional approach to understand the complex and multi-faceted nature of fluency as mediated by WCF processing.